De officiis Doctors' Oaths and Appointments in Early Modern Nuremberg - Dross, Fritz (Civic Medicine. Physician, Polity, and Pen in Early Modern Europe, 2020)
This chapter provides the first in-depth analysis of civic doctors’ oaths and appointment contracts and how these changed over time in relation to the growth of corporative organization and written constitution. Nuremberg, a city-state that bound all resident doctors, barber-surgeons, apothecaries, and midwives to the commonwealth by oath of office, provides the case study. By the mid-fifteenth century, the physician’s bond to the community and specific duties were validated and perpetuated by an oath text, its annual oral performance, a decree confirming it had been sworn, annual listing of those who had sworn, and a brief record of the swearing. The oath defined all physicians’ activity as public benefit under public regulation. The sixteenth century added appointment contracts. The oath unified; contracts differentiated—by specialization, salary, period—yet also unified because they were all with the city. From 1593, civic oath and contracts were subsumed by organization of all doctors into a college of physicians (Collegium Medicum) and a published medical constitution (Medizinalordnung). The new constitutional and professional logic accommodated the old civic one. In these ways, the city was a medical polis and not only a corporative system and medical marketplace.<br
CRIS-Team WoS Importer:2021-08-13